THE IMPACT OF OBESITY ON RESPIRATORY MUSCLE STRENGTH IN YOUNG ADULTS - Ferreira, Yohanna Ribeiro; Granado, Paula Rocha; Soares, Viviane (CIPEEX, 2025)
Introduction: Obesity, characterized by excess body fat, affects all age groups and is currently a public health problem. This condition is identified through anthropometric measures such as Body Mass Index (BMI) and waist-to-hip ratio. In addition to increasing the risk of chronic diseases, it contributes to changes in the musculoskeletal system. The global rise in obesity among adolescents and young adults suggests potential impairments in pulmonary function in these individuals. Objectives: To associate the presence of obesity with respiratory muscle strength in young adults. Methodology: This is a cross-sectional observational study. The study population consisted of 70 medical students from UniEVANGÉLICA, selected according to inclusion and exclusion criteria. Body Mass Index (BMI) and respiratory muscle strength were evaluated through maximum inspiratory pressure (MIP) and maximum expiratory pressure (MEP). Results: Overweight young adults showed significantly higher values for MIP and predicted %MIP compared to eutrophic participants, indicating that obesity is associated with greater respiratory muscle strength. Conclusion: In this study, young adults with excess weight presented better MIP values, mostly within expected ranges. Obesity, a global health problem, increases the risk of respiratory and cardiovascular diseases, and these results contribute to developing health strategies to mitigate such risks.